Long non‐coding RNA RUNX1‐IT1 plays a tumour‐suppressive role in colorectal cancer by inhibiting cell proliferation and migration. (30th November 2018) - Shi, Jinxin; Zhong, Xi; Song, Yongxi; Wu, Zhonghua; Gao, Peng; Zhao, Junhua; Sun, Jingxu; Wang, Jiajun; Liu, Jingjing; Wang, Zhenning
Abstract : Long non‐coding RNAs (lncRNAs) have been demonstrated to be involved in the progression of various cancers. In this study, we aim to investigate the role of lncRNA RUNX1‐IT1 in the development of colorectal cancer (CRC). The expression levels of lncRNA RUNX1‐IT1 were measured using quantitative real‐time Polymerase Chain Reaction(qRT‐PCR). CCK8 proliferation assay, transwell assay, and flow cytometry were performed to evaluate the effect of lncRNA RUNX1‐IT1 on CRC cell proliferation, migration, and apoptosis. The proliferation markers (PCNA, Ki67), apoptosis markers (cleaved‐PARP, cleaved‐caspase3), and MMP9 are detected by western blotting. Significant down regulation of lncRNA RUNX1‐IT1 was measured in CRC tissues and three CRC cell lines (HCT116, HT29, and RKO) compared with paired nontumorous adjacent tissues ( P  < 0.01) or the normal colonic epithelial cell line FHC ( P  < 0.05), respectively. Moreover, the proliferative and migration potential of CRC cells were inhibited by overexpressing lncRNA RUNX1‐IT1, which could be obviously improved by knocking down lncRNA RUNX1‐IT1. The protein levels of PCNA, Ki67, and MMP9 were upregulated by overexpressing lncRNA RUNX1‐IT1 and down regulated in si‐RUNX1‐IT1 cells. Besides, lncRNA RUNX1‐IT1 could also promote the apoptosis of CRC cells. In conclusion, lncRNA RUNX1‐IT1 is downregulated in CRC and plays a tumour‐suppressive role due to the regulatory of cell proliferation, migration, and apoptosis. Significance of the study: We demonstrated that lncRNA RUNX1‐IT1 was down regulated both in CRC tissues and cell lines. Besides, lncRNA RUNX1‐IT1 could serve as a potential diagnostic biomarker and play a tumour‐suppressive role owing to its good diagnostic efficacy and inhibition of CRC cell proliferation and migration.